IMPLEMENTASI TUGAS SUB BAGIAN KOMISI DAN KEPANITIAN MELAKSANAKAN PENYUSUNAN PROGRAM KERJA KEGIATAN BERDASARKAN PERATURAN GUBERNUR NOMOR 60 TAHUN 2016 PASAL 17 AYAT (2) DI DPRD PROVINSI LAMPUNG - S. Endang Prasetyawati; NAZIRHAN NAZIRHAN (KEADILAN PROGRESIF, 2022)
The Commission is a permanent organ of the DPRD and is formed by the DPRD at the beginning of the DPRD membership term. Every member of the DPRD except the leadership of the DPRD is obliged to become a member of one of the commissions. The Plenary Meeting of the DPR RI. And the committee carries out the affairs of providing DPRD facilities and the DPRD Secretariat, Administration, Personnel, Household and Finance. The research problem is how the implementation of the tasks of the sub-division of the commission and the committee in carrying out the preparation of the work program based on the Governor's Regulation Number 60 of 2016 Article 17 Paragraph (2) in the Lampung Provincial DPRD. The research methoduses a normative and empirical juridical approach. The data used are secondary data and primary data. The data analysis used is qualitative juridical analysis. The results of the research Implementation of the tasks of the sub-commissions and committees carrying out the preparation of activity work programs based on the governor's regulation number 60 of 2016 article 17 paragraph (2) in the Lampung provincial DPRD that the task of committee functions such as the General and Finance section, Administration section, Household section, section Finance, Sessions section, Meetings section, Minutes section, Budget Facilitation section and Legislative Oversight, Law -Invitation and Public Relations section, Legislative Studies section - Invitation, Publication section and Public Relations (HUMAS), Library and Documentation section as stipulated in the regulations governor number 60 of 2016 article 17 paragraph 2 so that it runs as it should.